2022
DOI: 10.3889/oamjms.2022.8001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Intake on Body Mass Index in Universitas Sumatera Utara Medical Students

Abstract: Overweight and obesity is one of the health problems in the world. This condition is associated with various health problems such as cardiovascular disease, stroke, osteoarthritis, chronic back pain, gallbladder disease, and cancer. Consuming adequate fluids can help you lose weight. This study aimed to determine the relationship between body fluid intake and body mass index (BMI) in Medical Faculty Universitas Sumatera Utara students. A cross-sectional study was conducted on USU Medical Faculty students from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Regular adequate water intake also acts as protective factor of chronic kidney disease (6). Furthermore, some studies showed association between adequate water intake and body weight improvement and lower risk of overweight (7)(8)(9). Enhörning et al reported that water supplementation is potential for diabetes mellitus prevention among low drinker (10).…”
Section: Introductionmentioning
confidence: 99%
“…Regular adequate water intake also acts as protective factor of chronic kidney disease (6). Furthermore, some studies showed association between adequate water intake and body weight improvement and lower risk of overweight (7)(8)(9). Enhörning et al reported that water supplementation is potential for diabetes mellitus prevention among low drinker (10).…”
Section: Introductionmentioning
confidence: 99%